Simulasi Gerak Kepiting Menggunakan Metode Inverse Kinematics - STKIP PGRI Pacitan, Muga Linggar Famukhit; STMIK AMIKOM Yogyakarta, M Suyanto; Universitas Surakarta, Sukoco (IJNS - Indonesian Journal on Networking and Security, 2016)
ABSTRACT - "Crab Motion Simulation Method Using Inverse Kinematics" is a study in order to know how to move animals crab to be applied in 3D animation, the next goal is to measure the angle degree of freedom crab animal bones and generates motion patterns using Inverse Kinematics. Limitation of the study variable is the object of study on the crab manifold Parathelphusa Convexa, the method used is the method of Inverse Kinematics, simulations created using 3ds Max software and 3D shape measurement joints rotary joints only on the base of the foot. The method of analysis in this research is using research and development.Results of the research is the way data and data running crab animal bones freedom angle (degrees of freedom) to be applied in 3D animation. The end result of the research is to create the pattern of the road (walk cycle) animals crab, 3D simulation is generated in the form of roads, running and walking on an incline.The conclusion of the study is the method of Inverse Kinematics can be applied in the form of a 3D simulation of movement of animals walking crab. Research generates the data angle degrees of freedom bone. Generating motion patterns running animals crab manifold Parathelphusa Convexa, ie two legs (1, 3) on the right side paired with a foot (6, 8) on the left side and leg (2, 4) on the right side paired with legs (5, 7) on the left side.Keywords: Inverse Kinematic, crab, Degrees Of Freedom, Walk CycleÂ ABSTRAKSI â€œSimulasi Gerak Kepiting Menggunakan Metode InverseÂ  Kinematicsâ€ merupakan penelitian dengan tujuan mengetahui cara gerak hewan kepiting untuk diterapkan dalam animasi 3D, tujuan selanjutnya adalah mengukur sudut derajat kebebasan tulang hewan kepiting dan menghasilkan pola gerak dengan menggunakan metode Inverse Kinematics. Batasan variable penelitian adalah obyek penelitian pada kepiting berjenis Parathelphusa Convexa, metode yang digunakan adalah metode Inverse Kinematics, simulasi dibuat dengan menggunakan software 3Ds Max berbentuk 3D dan pengukuran sendi hanya pada sendi putar bagian pangkal kaki. Metode analisis dalam penelitian ini adalah menggunakan metode research and development. Hasil dari penelitian adalah data cara berjalan hewan kepiting dan data sudut kebebasan tulang (degrees of freedom) untuk diterapkan dalam animasi 3D. Hasil akhir dari penelitian adalah tercipta pola jalan (walk cycle) hewan kepiting, simulasi 3D yang dihasilkan berupa jalan, lari dan berjalan pada bidang miring.Kesimpulan dari penelitian adalah metode Inverse Kinematics dapat diterapkan dalam simulasi 3D berupa gerak berjalan hewan kepiting. Penelitian menghasilkan data sudut derajat kebebasan tulang. Menghasilkan pola gerak berjalan hewan kepiting berjenis Parathelphusa Convexa, yaitu dua kaki (1, 3) pada sisi kanan berpasangan dengan kaki (6, 8) pada sisi kiri dan kaki (2, 4) pada sisi kanan berpasangan dengan kaki (5, 7) pada sisi kiri.Â Â Kata kunci: Inverse Kinematik, Kepiting, Degrees Of Freedom, Walk Cycle